Kemampuan, Pengalaman, Independensi, dan Due Profesional Care Auditor pada Pelaksanaan Prosedur Audit Investigatif - Sardju, Fitriani (Insan Cita Bongaya Research Journal, 2022)
Abstract: This study aims to examine the effect of Auditor Ability, Auditor Experience, Auditor Independence, and Due Professional Care Auditor on the Effectiveness of the Implementation of Investigative Audit Procedures. The population in this study was the examiner who worked at the BPKP (Financial and Development Supervisory Agency) office in North Maluku and North Sulawesi Provinces. This study uses multiple linear regression models. The results of the study indicate that the auditor's ability has a positive effect on the effectiveness of conducting investigative audit procedures. The auditor's experience has a positive effect on the effectiveness of conducting investigative audit procedures. Auditor independence does not affect the effectiveness of investigative audit procedures. Due professional care auditor has a positive effect on the effectiveness of conducting investigative audit procedures. Keywords: auditor ability, auditor experience, auditor independence, due professional care auditor and effectiveness of audit investigative procedures